Faktor Penentu Profitabilitas pada Perusahaan Perbankan yang Terdaftar di BEI Periode 2019-2021 - Alfina Arum Rahmadhani; Yuli Chomsatu; Suhendro Suhendro (Universitas Batanghari Jambi, 2023)
This research set out to determine how factors including company size, liquidity, leverage, capital adequacy ratio, capital structure, and total asset turnover affect a business's capacity to earn a profit. The population in tthis study arer banking companies listed on the Indonesia Stock Exchangee(IDX) in 2019-2021. This study used aapurposive sampling technique: banking sector companies listed on the Indonesia Stock Exchange (IDX) in a row for 2019-2021, banking companies that issued complete financial reports in 2019-2021, and profit banking companies. The data analysis method used innthis study is multiple linear analysis. The results offthis study indicate that firm size, liquidity and total asset turnover affect profitability, while leverage, capital adequacy ratio and capital structure do not affect profitability.